2000
DOI: 10.1088/0967-3334/21/3/302
|View full text |Cite
|
Sign up to set email alerts
|

A resonator sensor for measurement of intraocular pressure - evaluation in anin vitropig-eye model

Abstract: Intraocular pressure (IOP) measurement is performed routinely at every eye clinic. High IOP, which can be a sign of glaucoma, can lead to degeneration of the retina and can cause blindness. In this study we developed a resonator sensor for IOP measurement based on an oscillator consisting of a piezoelectric element made of lead zirconate titanate, a flat contact piece of nylon and a feedback circuit. The aim of this study was to evaluate the new sensor's ability to determine lOP in an in vitro pig-eye model. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 12 publications
3
50
0
Order By: Relevance
“…The effect is known from current tonometry methods such as the iCare tonometer (Munkwitz et al, 2008), Tono-pen (Giaconi et al, 2016), or air-puff tonometers (Derka, 1980) that the sensitivity decreases at higher IOP levels (Yung et al, 2014;Giaconi et al, 2016;Eklund et al, 2000). This is explained by the fact that the possible deformation of the eye with a constant force decreases, which leads to a lower signal-to-noise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The effect is known from current tonometry methods such as the iCare tonometer (Munkwitz et al, 2008), Tono-pen (Giaconi et al, 2016), or air-puff tonometers (Derka, 1980) that the sensitivity decreases at higher IOP levels (Yung et al, 2014;Giaconi et al, 2016;Eklund et al, 2000). This is explained by the fact that the possible deformation of the eye with a constant force decreases, which leads to a lower signal-to-noise ratio.…”
Section: Discussionmentioning
confidence: 99%
“…First, a clinical evaluation of the same resonator sensor probe that was used in a previous in vitro study (EKLUND et al, 2000) was performed. Secondly, the same probe was used in an in vitro pig-eye model, where its sensitivity to off-centre positioning was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…That study suggested that the larger the contact area, the more vibrational energy is transferred to the sample, thereby increasing the influence of the sample on the frequency characteristics of the sensor system, resulting in a larger frequency shift. In a later study (EKLUND et al, 2000), that argument was extended, modelled and verified for the applanation resonator sensor (ARS), by showing the relationship between a linear phase shift of the sensor element AqbsE and the resulting frequency shift of the sensor system Ajs. The relationship is based on a resonance condition that states that the sum of phase shift around the circuit must be zero and an assumption that AqbsE is a linear function of contact area.…”
Section: Medical and Biological Engineering And Computing 2003 Vol 41mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that these sensors can distinguish between normal and cancerous prostate tissue, and could therefore constitute a new diagnostic instrument [1]. Moreover, such sensors can be used to measure the intra-ocular pressure, providing information for the evaluation of edema [2], [3].…”
Section: Introductionmentioning
confidence: 99%